Control of rice blast disease caused by Magnaporthe oryzae by application of antifungal nanomaterials from Emericella nidulans - Jiao Jiao Song; Kasem Soytong; Somdej Kanokmedhakul (Plant Protection Science, 2021)
Control of rice blast disease caused by Magnaporthe oryzae by application of antifungal nanomaterials from Emericella nidulans | Jiaojiao Song, Kasem Soytong, Somdej Kanokmedhakul | Agricultural Journals
Keywords: Plant-Microbe Interactions and Immunity; Plant Pathogens and Fungal Diseases; Silicon Effects in Agriculture